1996
DOI: 10.1007/bf00035278
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTLs in breeding for drought tolerance in maize (Zea mays L.)

Abstract: Grain yield in the maize (Zea mays L) plant is sensitive to drought in the period three weeks either side of flowering . Maize is well-adapted to the use of restriction fragment length polymorphisms (RFLPs) to identify a tight linkage between gene(s) controlling the quantitative trait and a molecular marker . We have determined the chromosomal locations of quantitative trait loci (QTLs) affecting grain yield under drought, anthesis-silking interval, and number of ears per plant . The F3 families derived from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
1
13

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(61 citation statements)
references
References 35 publications
3
44
1
13
Order By: Relevance
“…The same QTLs for yield were identified on 2.09 bin by Beavis (3) and on chromosome 5 by Agrama et al (1). qtl for yield on chromosome 7 in our study was detected in the region between 7.2 -7.03 bins, while several authors detected qtl for yield between 7.04 -7.05 bins (2,3,13,20).…”
Section: Comparison Between the Qtlssupporting
confidence: 89%
“…The same QTLs for yield were identified on 2.09 bin by Beavis (3) and on chromosome 5 by Agrama et al (1). qtl for yield on chromosome 7 in our study was detected in the region between 7.2 -7.03 bins, while several authors detected qtl for yield between 7.04 -7.05 bins (2,3,13,20).…”
Section: Comparison Between the Qtlssupporting
confidence: 89%
“…The mapping and tagging of QTL form the basis of MAS. The identification of QTL for maize drought tolerance has been investigated in many studies and some progress has been made (Agrama et al 1996;Ribaut et al 1996Ribaut et al , 1997Frova et al 1999;Sanguineti et al 1999;Sari-Gorla et al 1999;Gao et al 2003;Li et al 2003Li et al , 2004Zhang et al 2004). However, most of these previous studies have been based on the additive-dominant genetic model on the assumption that there is no interactive effect among the alleles.…”
Section: Mapping Of Qtl and Genetic Effect Of Yield Components In Thementioning
confidence: 99%
“…The mapping and tagging of QTL for maize drought tolerance has been reported in many studies (Agrama et al 1996;Ribaut et al 1996Ribaut et al , 1997Sanguineti et al 1999;Sari-Gorla et al 1999;Gao et al 2003;Li et al 2003Li et al , 2004Zhang et al 2004). Agrama and Moussa (1996) reported that there were five QTLs related to grain yield on chromosomes 1, 3, 5, and 8 under drought conditions that could explain 49.6% of the phenotypic variance. Ribaut et al (1997) studied the QTL of grain yield, ear number, kernel number, and 100-kernel weight under well-watered conditions and two other water-stress regimens and identified one to seven QTL for each trait in the different environments.…”
mentioning
confidence: 99%
“…Using genetic mapping to dissect the inheritance of different complex traits in the same segregating population can be a powerful means to distinguish common heredity from casual associations between such traits (Paterson et al 1988). Genetic mapping has been used to identify quantitative trait loci (QTLs) responsible for improved productivity under arid conditions (Agrama and Moussa 1996;Tuinstra et al 1996;Ribaut et al 1997). Separately, QTLs have also been reported that confer physiological variations thought to be associated with stress tolerance, such as osmotic adjustment (defined as the active accumulation of solutes in response to water deficit as opposed to passive solute concentration caused by water loss; Morgan 1992;Lilley et al 1996;Morgan and Tan 1996), WUE (measured either directly or indirectly as a carbon isotope ratio, 13 C/ 12 C, expressed with a differential notation as ␦ stomatal conductance (Ulloa et al 2000), and various measures of plant water status (Lebreton et al 1995;Teulat et al 1998a).…”
mentioning
confidence: 99%